e-Health and Personal Information: a tug of war between Privacy and Big Data - Gonçalves, Maria Eduarda; Raimundo, J. (Coping With Health Risks in the Era of Social Networks, 2014)
In this day and age of mass surveillance-filled headlines, the paradigm of Big Data plays a key role, being increasingly embraced by every sector that has moved its activity to the online environment, envisioning the Internet as a very appealing place to expand businesses and attract new customers. The pervasiveness of information and communication technologies (computers, tablets, smartphones, GPS systems, etc.) allows for an intensive collection, storage and retrieval of personal data, which, when used with disregard of one’s private life, may lead to an unprecedented exposure and, consequently, to the establishment of behavioural trends and consumer profiling. The health industry, being one of the industries in constant development, both scientific and technologically, has also been spreading its activity to online platforms, such as social networks, web forums and dedicated health information websites, in order to reach patients more easily and also to join in on this new “gold rush” we have been witnessing, regarding the collection of personal data of users/consumers/patients, which, when it comes to health, is of the highest sensitivity. Thus, not only private, but also public institutions are putting massive efforts into the adoption of e-health technologies, even though there is currently a more than appearing overlap surrounding both these sectors, especially due to the sharing of patients’ health data and even due to some partnerships on healthcare management. In this paper, we aim to bring to the discussion several issues that surround the application of ICT to the health industry, highlighting not only the opportunities it entails, but also the governance challenges and the serious risks it may bring to fundamental rights, namely data protection and privacy, showing the progress that has been made on both sides of the Atlantic, as far as regulation is concerned. The strenuous quest for balance between public interest and private rights may also have a say in this, as the relentless expansion of Big Data in our lives may lead us to wonder whether this is the end of privacy as we know it.